Cone-beam tomography assessment of condylar position discrepancy between centric relation and maximal intercuspation - João César Guimarães Henriques; Alfredo Júlio Fernandes Neto; Guilherme de Araújo Almeida; Naila Aparecida de Godoi Machado; Éverton Ribeiro Lelis (Sociedade Brasileira de Pesquisa Odontológica, 2012)
The magnitude of occasional discrepancies between the centric relation and maximal intercuspation positions remains a controversial subject. This study quantitatively evaluated the possible discrepancies in the condyle/mandibular fossa relationship between these positions using cone-beam computed tomography. Twenty young and asymptomatic volunteers were distributed equally into normal occlusion and Angle Class I, II and III malocclusion groups. They were submitted to one tomographic scan in maximal intercuspation and one in centric relation. Measurements were performed on lateral and frontal cuts of the patients' temporomandibular joints, and the data collected were compared using Student's t test at a significance level of 5%. The results showed that there were no statistically significant differences between the centric relation and maximal intercuspation positions in young and asymptomatic patients with practically intact dentitions using cone-beam computed tomography.